Testing the efficacy of the "EA Brief": an intervention to improve emotional attachment and emotional availability (EA) - McDonnell, Maren, author; Biringen, Zeynep, advisor; Riggs, Nathaniel, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2018)
The goal of this study was to determine the extent to which a brief parenting intervention provided the context for helping families to support positive mother-child interactions as well as more optimal mother and child outcomes. Participants in this study were middle-income mothers and their children ages 0-3 years of age (N = 25 dyads). Participants were filmed via Skype during a 20-minute mother-child free play and completed questionnaires (Time 1) before attending the brief intervention (involving: 3 hours of a group workshop, brief reading materials, one hour of one-on-one coaching, and two weeks of tailored texts) followed by a repeat of the 20-minute Skype interaction and the completion of the same questionnaires (Time 2). Paired samples t-tests were performed, revealing that mothers reported improvements in their personal well-being (using the Flourishing Scale), reports about the mother-child relationship (using the Emotional Availability Self Report), and observed interactions, particularly the child's side of the relationship (using the Emotional Availability Scales), from pretest to posttest. Results are discussed in terms of a brief intervention potentially having a role in "planting a seed" for parenting enhancement and child development.